2006
DOI: 10.1002/mds.20935
|View full text |Cite
|
Sign up to set email alerts
|

Expectation and the placebo effect in Parkinson's disease patients with subthalamic nucleus deep brain stimulation

Abstract: Parkinson's disease (PD) is among the disorders in which the placebo effect can play a significant role. [1][2][3][4] Functional imaging studies have demonstrated that this effect is related to dopamine release in the striatum. 5 This dopamine release appears to be linked to expectation of reward (i.e., clinical benefit), which is in turn mediated by dopamine release in the ventral striatum.Since the initial description of high-frequency deep brain stimulation (DBS) of the subthalamic nucleus (STN) for the tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(73 citation statements)
references
References 28 publications
3
65
1
2
Order By: Relevance
“…This result differs from the findings of previous studies where a modulation of bradykinesia by expectation was reported [18][19][20][21]; yet in those studies either exclusively hypokinetic-rigid or a mixture of hypokinetic-rigid and tremor-dominant PD patients were analyzed suggesting that placebo and nocebo responses mainly manifest on symptoms of predominant relevance to the patients, that is, tremor in the patients of the present study. Moreover, although expectations regarding the effect of STN-DBS were not exclusively induced with respect to tremor but also regarding motor symptoms in general, patients may have specifically focused their expectation on tremor rather than on other symptoms such as bradykinesia.…”
Section: Effect Of Expectation On Bradykinesiacontrasting
confidence: 99%
See 3 more Smart Citations
“…This result differs from the findings of previous studies where a modulation of bradykinesia by expectation was reported [18][19][20][21]; yet in those studies either exclusively hypokinetic-rigid or a mixture of hypokinetic-rigid and tremor-dominant PD patients were analyzed suggesting that placebo and nocebo responses mainly manifest on symptoms of predominant relevance to the patients, that is, tremor in the patients of the present study. Moreover, although expectations regarding the effect of STN-DBS were not exclusively induced with respect to tremor but also regarding motor symptoms in general, patients may have specifically focused their expectation on tremor rather than on other symptoms such as bradykinesia.…”
Section: Effect Of Expectation On Bradykinesiacontrasting
confidence: 99%
“…On group level, expectation did not significantly affect resting tremor in the patients of the present study. This finding is in agreement with a study by Mercado et al [19] who did not observe a modulation of tremor using a different paradigm to manipulate patients' expectation regarding STN-DBS. However, given the relatively small number of placebo and nocebo responders in the present study, the lack of statistical significance on group level is not surprising.…”
Section: Effect Of Expectation On Tremorsupporting
confidence: 93%
See 2 more Smart Citations
“…Without the patient or the evaluating physician knowing in which group they are, some of the systems can be left off for some specified period of time in a crossover design. Given the strength of the placebo effect in patients with movement disorders and psychiatric disease, [33][34][35] this is an …”
Section: History and Future Of Dbsmentioning
confidence: 99%